Myeloid-Derived Suppressor Cells in Bladder Cancer: An Emerging Target - Clément Klein; Samy Mebroukine; Mathilde Madéry; Alexandra Moisand; Thomas Boyer; Nicolas Larmonier; Grégoire Robert; Charlotte Domblides (Cells)
Bladder cancer remains a prevalent and challenging malignancy. Myeloid-derived suppressor cells (MDSCs) have emerged as key contributors to the immunosuppressive tumor microenvironment, facilitating tumor progression, immune evasion, and resistance to therapies. This review explores the role of MDSC in bladder cancer, highlighting their involvement in immune regulation; tumor progression; and resistance to therapies such as bacillus Calmette–Guérin (BCG) therapy, chemotherapy, and immune checkpoint inhibitors (ICIs). We also discuss their potential as biomarkers and therapeutic targets, with current evidence suggesting that targeting MDSCs, either alone or in combination with existing treatments such as BCG and ICIs, may enhance anti-tumor immunity and improve clinical outcomes. However,, challenges remain, particularly regarding the identification and therapeutic modulation of MDSC subpopulations. Further research is warranted to fully elucidate their role in bladder cancer and to optimize MDSC-targeted therapies.